Los caballos - Greydanus, Rose.; Snyder, Joel. (Mexico, D.F. : SITESA, 1987)
Simple text and illustrations introduce the characteristics of horses.
Translation of: Horses.
Keywords: Horses -- Juvenile literature; Literature